2001
DOI: 10.1243/0954405011519448
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical and experimental investigation of thrust and torque in vibration microdrilling

Abstract: A method for predicting the thrust and torque in vibration microdrilling is proposed. The model is based on the mechanics of vibration cutting analysis, which involves the development of a dynamic uncut chip thickness analysis for each vibration cutting element at the lips and chisel edge. The proposed method has been tested for a range of vibration parameters and feeds. The predicted thrust and torque values have been compared with those obtained in vibration microdrilling experiments. These comparisons showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…Zhang et al [107] noticed the effect of vibrations and developed a model based on the mechanics of vibrations and the continuous distribution of thrust and torque along the cutting edge and the chisel edge of the twist drill. Wang et al [108,109] concluded that vibration drilling is different from conventional drilling and presented a method, which involves the development of a dynamic uncut chip thickness for each cutting element at the cutting edge and chisel edge. The model described by the authors the dynamic cutting process, where the mean thrust and torque increased as feed increases under constant vibration.…”
Section: Figure 17 Cutting Forces During Drillingmentioning
confidence: 99%
“…Zhang et al [107] noticed the effect of vibrations and developed a model based on the mechanics of vibrations and the continuous distribution of thrust and torque along the cutting edge and the chisel edge of the twist drill. Wang et al [108,109] concluded that vibration drilling is different from conventional drilling and presented a method, which involves the development of a dynamic uncut chip thickness for each cutting element at the cutting edge and chisel edge. The model described by the authors the dynamic cutting process, where the mean thrust and torque increased as feed increases under constant vibration.…”
Section: Figure 17 Cutting Forces During Drillingmentioning
confidence: 99%
“…(Affecting forces to the cutting edge) [24] delme işlemi esnasında, matkap ağız bölgesini esas, ikincil kesme kenarı ve matkap uç bölgesi şeklinde üç bölge olarak belirterek, talaş oluşumu ve matkabın ağızlaması ile ilgili, Zhang ve ark., [25], matkabın kesme kenarı boyunca, ilerleme kuvveti, moment ve titreşim mekaniği ile ilgili, Wang ve ark., delme esnasında oluşan talaş kalınlığına bağlı olarak dinamik kesilmemiş talaş kalınlığı arasındaki ilişkiyi belirten modeller geliştirmişlerdir. Sabit titreşim parametrelerinin yanı sıra ilerlemenin artması ile moment ve ilerleme kuvvetleri artmaktadır [26][27]. Coz ve ark [28]., Ti6Al4V alaşımının MQL (minimal quantity of lubricant) ile delinmesinde kesme hızının artması ile sıcaklık ve moment değerlerinde artış olduğunu ve bu değerlerin Zeilmann and Weingaertner [29]' in yaptığı benzer çalışmaya göre daha yüksek olduğunu belirtmişlerdir.…”
Section: Kesme Kuvveti Ve Moment (Cutting Force and Moment)unclassified
“…According to the research of Amini et al, 13 the vibration and drilling force signals have more influence than other processing parameters and signals. Wang et al 14 found that multisignals and multifeatures can better correlate the predicted value with the actual value by analyzing the characteristic values of thrust force and vibration in microdrilling research. Jain and Lad 15 proposed a new integrated tool condition monitoring system to help improve system performance and diagnostic reliability and predict tool wear better.…”
Section: Introductionmentioning
confidence: 99%